The Effect of Cognitive Instruction in the Development of Employment Interview Skills in Adolescents with Learning Disabilities - Taves, Ruth Anne H.; Hutchinson, Nancy L.; Freeman, John G. (Canadian Journal of Counselling and Psychotherapy, 1992)
A series of six modules, Pathways was designed to facilitate career maturity in youth with learning disabilities. In each module, cognitive instruction was used to teach adolescents strategies and when to use these strategies. One of the modules, Succeeding with the Interview, prepares adolescents for employment interviews. This paper reports on a pilot study designed to evaluate the effectiveness of the module in teaching employment interview skills to four students with learning disabilities. Compared to two control groups, students who participated in the interview module showed changes on measures of behaviour, cognition, and metacognition.